Studying Covariational Affection and Reason: A Reflection on the Importance - Nava Guzmán, Cristian (2021)
This essay focuses on the importance of analyzing emotions in terms of covariational reasoning among mathematics students. An introduction is provided to this area of research in mathematics education known as the affective domain with a general overview on its relevance. It is generally concluded that an overall lack of research exists to address relationships of student affection and its impact on Calculus performance. Practical and theoretical recommendations are then provided to approach the reasons why we should study emotions and their connection with covariational reasoning and suggestions as to how to approach this feat.